Exploring the social networks of bereaved spouses: Phenomenological case studies - Morrigan, Brigid; Keesing, Sharon; Breen, Lauren (SAGE, 2020)
Bereavement is a significant stressor that can affect and be affected by social support, yet there is little known about the social networks of bereaved individuals. We conducted an in-depth qualitative examination of the social networks of bereaved spouses through an interpretive phenomenological analysis. Five participants were interviewed about their social networks prior to and following bereavement. Participants described considerable changes in their social networks. They reported connecting with others who had experienced similar stressors, including via online support groups for widows/widowers, as a key strategy for re-engagement with their social worlds. The death of a spouse can precipitate the dramatic reorganization of social networks to incorporate and adapt to this crisis. Findings offer guidance for service providers to support bereaved spouses to harness existing social networks to optimize received support.